1993
DOI: 10.1007/bf02942162
|View full text |Cite
|
Sign up to set email alerts
|

Cell proliferation in breast tumours: Analysis of histological parameters Ki67 and PCNA expression

Abstract: Ki67 and Proliferating Cell Nuclear Antigen (PCNA) are antigens expressed in the nucleus during various phases of cell division, which can be detected immunohistochemically using monoclonal antibodies. Thirteen fibroadenomas and 39 carcinomas were examined for expression of Ki67 and PCNA. A staining index was calculated for each tumour as the percentage of positive cells in the areas of highest density. The mean index for both antibodies was significantly lower in fibroadenomas than in malignant tumours. A wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
2
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 21 publications
1
23
2
1
Order By: Relevance
“…However, poor correlation with other proliferation index such as Ki-67 expression and mitotic index has been observed [Sullivan et al, 1993].…”
Section: Proliferating Cell Nuclear Antigen (Pcna)mentioning
confidence: 99%
“…However, poor correlation with other proliferation index such as Ki-67 expression and mitotic index has been observed [Sullivan et al, 1993].…”
Section: Proliferating Cell Nuclear Antigen (Pcna)mentioning
confidence: 99%
“…Cells that showed specific nuclear staining were scored as positive and the Ki67 labelling index was expressed as the percentage of the total number of tumour cells that stain positive; this equates to the growth fraction of the tumour. Higher grade cancers have higher Ki67 indices – one study found mean scores of 9% in grade I tumours, 14% in grade II and 26% in grade III [23]. The Ki67 index correlates significantly with estimates of the mitotic index [24] and SPF by flow cytometry [13,25,26], although some of the published correlation coefficients are modest (r = 0.42 [13], r = 0.22 [26]).…”
Section: Nuclear Antigensmentioning
confidence: 99%
“…1A, S-phase cells in HCT116 xenografts can be observed nearer to blood vessels, whereas quiescent cells predominate in areas further from vessels. Despite uncontrolled proliferation being a hallmark of cancer, human tumors often exhibit proliferative indices as low as 5% to 10% (14). Even micrometastases of a quarter of a millimeter in size will possess regions of hypoxia and nutrient deprivation leading to tumor cell quiescence (10,15).…”
Section: Introductionmentioning
confidence: 99%